The Role of Tumor Inflammatory Microenvironment in Lung Cancer - Tan, Zhaofeng; Xue, Haibin; Sun, Yuli; Zhang, Chuanlong; Song, Yonglei; Qi, Yuanfu (Frontiers in Pharmacology, 2021)
Lung cancer is the most common and fatal malignant tumor in the world. The tumor microenvironment (TME) is closely related to the occurrence and development of lung cancer, in which the inflammatory microenvironment plays an important role. Inflammatory cells and inflammatory factors in the tumor inflammatory microenvironment promote the activation of the NF-κB and STAT3 inflammatory pathways and the occurrence, development, and metastasis of lung cancer by promoting immune escape, tumor angiogenesis, epithelial–mesenchymal transition, apoptosis, and other mechanisms. Clinical and epidemiological studies have also shown a strong relationship among chronic infection, inflammation, inflammatory microenvironment, and lung cancer. The relationship between inflammation and lung cancer can be better understood through the gradual understanding of the tumor inflammatory microenvironment, which is advantageous to find more therapeutic targets for lung cancer.